HUBUNGAN SIKAP TERHADAP BLENDED LEARNING DAN TINGKAT STRES DENGAN PERILAKU PROKRASTINASI AKADEMIK MAHASISWA FAKULTAS KEDOKTERAN UPNVJ - Rania Azaria Triswiandi, (2023)
Academic procrastination refers to the inclination to delay academic tasks and is frequently linked with feelings of anxiety, which can adversely affect academies performances. Procrastination can be influenced by various factors, such as stress and learning methods. The blended learning method is currently being implemented by the UPNVJ Faculty of Medicine. The objective of this study is to determine the relationship between attitudes towards blended learning and stress levels with academic procrastination behavior of medical students of Universitas Pembangunan Nasional "Veteran" Jakarta. This study is an observational analytical study with a cross-sectional design and proportional stratified random sampling method. The sample of this study amounted to 229 students from the classes of 2019, 2020, and 2021. This research instrument used an attitude questionnaire towards blended learning, DASS-21 questionnaire, and academic procrastination scale. The statistical tests used for bivariate analysis are Chi Square test and Kruskal Wallis. Multivariate analysis used a simple logistic regression test. The bivariate test shows the p-value between attitudes towards blended learning and academic procrastination behavior is 0.612 and the p-value between stress levels and academic procrastination behavior is 0.002. The multivariate test shows the odd ratio between stress levels and academic procrastination behavior is 3.134. Results show that there is no relationship between attitudes towards blended learning and academic procrastination behavior, but there is a relationship between stress levels and academic procrastination behavior. It can be concluded that attitudes towards blended learning do not affect academic procrastination behavior, while stress levels increase the risk of academic procrastination behavior by 3.13 times.